How does atopic dermatitis in childhood and adolescence affect educational success?. (21st August 2021) - Möhrenschlager, M.; Demolli, P.; Schmidt, V.
Abstract : Linked article : K. Pálsson et al . J Eur Acad Dermatol Venereol 2021; 35 : 1849–1858. https://doi.org/10.1111/jdv.17346